Do muro de tijolos ao muro digital: a ascensão do graffiti em Fortaleza e suas perspectivas em tempos pandêmicos - Baima, Caio Martiniano de Brito (2021)
The present paper entitled FROM THE BRICK WALL TO THE DIGITAL WALL: THE ASCENSION OF GRAFFITI IN FORTALEZA AND ITS PERSPECTIVES IN PANDEMIC TIMES comprises the report of an ethnographic research that took place in a multisituated way in the city of Fortaleza, in the physical environment and in the digital environment, through the Instagram social network, addressing the activity of graffiti artists in the context of the coronavirus pandemic. Starting, in the first section, from a historical recovery that leads to contemporary graffiti, this qualitative type investigation incorporates aspects pointed out by interlocutors, heard through semistructured interviews, in a dialogue with the bibliographic research. It continues, in the following sections, inserting the difficulties of conducting a research in the midst of the Covid-19 pandemic, simultaneously working on techniques designed to accompany the displacement of artistic productions from the city walls to the virtual space, in an observation provided by Instagram. At the end, two central aspects of the theme are discussed in the transition from 2020 to 2021: the difficulties in carrying out a project designed to take place through a face to face immersion in Praia de Iracema, constantly postponed due to the health protection measures adhered by the Government of the State of Ceará and, secondly, the exposure of the perceptions obtained in the virtual media trying understand the ways used for the maintenance of artistic works by graffiti artists who use Instagram. This work has as main objective to perceive and discuss the difficulties faced by these artists after the fateful arrivel of the pandemic, which requires confinement as the main containment measure. In this context, we intend to discuss the relationship between graffiti artists and the State, through the analysis of the text and the developments of the Public Notice Arte Urbana na PI, 2020, in the context of the emergency state, examining the elements of social control present in this type of government initiative and, in another aspect, the strategies used by graffiti artists to give continuity to the promotion of their art. Starting from DIÓGENES and seeking to understand cyberspace with RIFIOTIS, the method used, which underlies the procedures described above, was that of virtual ethnography. The study concludes by verifying aspects related to social control present not only in the public administration pathways, but also by the automated directions of digital media, and, at the same time, registering the incidence of numerous forms of attempted freedom found in the investigation, such as retourning to the streets during the lockdown, contradictorily less subject, in the circumstances of isolation, to the repression of the police, or the diffusion of content on social networks as an apparently safe space.